2015
DOI: 10.1016/j.celrep.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Recruitment of DOT1L to MLL-AF9 Defines Level of H3K79 Di- and Tri-methylation on Target Genes and Transformation Potential

Abstract: SUMMARY The MLL gene is a common target of chromosomal translocations found in human leukemia. MLL-fusion leukemia has a consistently poor outcome. One of the most common translocation partners is AF9 (MLLT3). MLL-AF9 recruits DOT1L, a histone 3 lysine 79 methyltransferase (H3K79me1/me2/me3), leading to aberrant gene transcription. We show that DOT1L has three AF9 binding sites, and present the NMR solution structure of a DOT1L-AF9 complex. We generate structure-guided point mutations and find they have graded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
115
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(131 citation statements)
references
References 37 publications
11
115
1
1
Order By: Relevance
“…A genome-wide study showed that inactivation of DOT1L leads to down-regulation of MLL-AF9 direct targets and an MLL1 translocation-associated gene expression signature [80]. Importantly, the AF9-binding site in DOT1L was mapped to 2 regions of human DOT1L (628–653 and 863–900 residues), and the interaction of DOT1L with the C-terminus of AF9 (present in MLL-AF9 fusion protein) is required for transformation by MLL-AF9 [127, 134]. These data suggest that MLL1-translocations create chimeric proteins that link MLL1 to other functionally distinct protein complexes including the super elongation complex (SEC) and the DOT1L-H3K79 methyltransferase complex and thus contribute to the ectopic expression of a homeobox gene-centric leukemic program (Fig.…”
Section: Molecular Basis Of Mll1-rearranged Leukemiasmentioning
confidence: 99%
“…A genome-wide study showed that inactivation of DOT1L leads to down-regulation of MLL-AF9 direct targets and an MLL1 translocation-associated gene expression signature [80]. Importantly, the AF9-binding site in DOT1L was mapped to 2 regions of human DOT1L (628–653 and 863–900 residues), and the interaction of DOT1L with the C-terminus of AF9 (present in MLL-AF9 fusion protein) is required for transformation by MLL-AF9 [127, 134]. These data suggest that MLL1-translocations create chimeric proteins that link MLL1 to other functionally distinct protein complexes including the super elongation complex (SEC) and the DOT1L-H3K79 methyltransferase complex and thus contribute to the ectopic expression of a homeobox gene-centric leukemic program (Fig.…”
Section: Molecular Basis Of Mll1-rearranged Leukemiasmentioning
confidence: 99%
“…The ChIP signal intensity of MLL-ENL was highly correlated with that of AF4 (r = 0.8398) through the DOT1L interaction domain (26), while MLL-ENL/ AF9 does so through the ANC1 homology domain (AHD), which is responsible for its association with both AF4 and DOT1L (11,12,27). Genetic ablation of Dot1l results in the loss of clonogenic activity of MLL-AF10-and MLL-AF9-transformed hematopoietic progenitors, indicating that the presence of DOT1L is required for MLL fusion-dependent leukemic transformation (28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic loss of AF10 caused a significant reduction of H3K79 di- and trimethylation, which corresponded to a reduction in HOXA gene expression and impairmentin the transforming potential of both MLL and non-MLL fusions. These findings were supported by elegant structure-function studies demonstrating that the stoichiometry of DOT1L binding to the MLL fusion complex can be manipulated to titrate the level and state of H3K79 methylation at MLL fusion target genes and thus leukemia development (Kuntimaddi et al, 2015). Furthermore, the critical transforming ability of AF10 as a component of the DOT1L complex suggests that the interface of the DOT1L-AF10 interaction may also be a therapeutic target.…”
Section: Targeting Histone Methylationmentioning
confidence: 86%